Analysis of Factors Affecting Breastfeeding Patterns During the 2021 Covid-19 Pandemic - Miranie Safaringga (Journal of Midwifery, 2022)
Breast milk is the most ideal nutrition for babies because it contains nutrients that are most suitable for the baby's needs and contains antibodies that can protect babies from various diseases, especially during the Covid-19 period.This study aims to determine the factors that influence breastfeeding patterns during the COVID-19 pandemic in 2021.The research design used Correlative Analytical with Crosssectional approach. The sample of this research used purposive sampling. The number of samples is 97 breastfeeding mothers in the city of Padang in 2021. Collecting data using a structured questionnaire to determinethe level of knowledge, attitudes, work status and breastfeeding patterns during COVID-19. The data analysis used was univariate and bivariate usingChi-square statistical test (p < 0.05). Based on the results of the Kruskal Wallis test, of the 4 variables that are associated with breastfeeding patternsduring Covid-19, only the knowledge variable has an Assymp sig = 0.049 (< 0.05), it can be concluded that there is a difference between a person's level of knowledge on breastfeeding patterns. during Covid-19. While the education, work and attitude variables have an Assymp Sig value > 0.05 which means there is no difference between education, work and attitudes with breastfeeding patterns during Covid-19.